Lack of Association of the Polymorphisms IL-17A (−197G/A) and IL-17F (+7488A/G) with Multibacillary Leprosy in Mexican Patients. (6th November 2014) - Escamilla-Tilch, Mónica; Estrada-García, Iris; Granados, Julio; Arenas-Guzmán, Roberto; Ramos-Payan, Rosalio; Pérez-Suárez, Thalía Gabriela; Salazar, Ma. Isabel; Pérez-Lucas, Riky Luis; Estrada-Parra, Sergio; Torres-Carrillo, Nora Magdalena
Abstract : Background. Leprosy is a chronic infectious disease caused by the intracellular acid-fast bacilli Mycobacterium leprae ; it has been determined that genetic factors of the host play an important role in the disease susceptibility. Thus, in this case-control study, we evaluated the possible association between the IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene SNPs and susceptibility to leprosy disease in Mexican population. Methods. Seventy-five leprosy patients and sixty-nine control subjects were included. Both SNPs were genotyped with the polymerase chain reaction-restriction fragment length polymorphism technique. Results. We found nonsignificant differences in genotype and allele frequencies related to IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene SNPs in MB as well as subclinical forms of leprosy disease versus healthy individuals. Conclusions. Since the sample size is not large enough, it is difficult to sustain an association of susceptibility to leprosy with genotypes or allele frequencies of IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780), suggesting that IL-17 polymorphisms have no significant role in the genetic susceptibility to development of this disease in the Mexican Mestizo population.